Bridging structure and mechanics of three-dimensional porous hydrogel with X-ray ultramicroscopy and atomic force microscopy. Issue 78 (26th August 2015) - Abuelfilat, A. Y.; Kim, Y.; Miller, P.; Hoo, S. P.; Li, J.; Chan, P.; Fu, J.
<x xml:space="preserve">Abstract</x> By combining phase contrast X-ray ultramicroscopy and nanoindentation with atomic force microscopy, the mechanics of individual hydrogel pores as well as their collective performance as a scaffold can be modelled and simulated.